THE ROLE OF EMOTIONAL INTELLIGENCE ON TRANSFORMATIONAL LEADERSHIP IN NURSING MANAGERS : A SISTEMATIC REVIEW - Irfan Madamang; Megawati; Andi Bintang (Universitas Islam Negeri Alauddin Makassar, 2023)
Introduction :The performance achievement produced by the organization cannot be separated from the role of a leader himself, how the leadership system is, knowledge about self-management in leading so that it will directly have an impact on improving the resulting performance. The aim of this study was to determine the role of emotional intelligence on transformational leadership. Methods : This literature review is based on the PRISMA checklist, searched through PubMed, ProQuest, Geogle Scholar. This research question is structured using the PICO method (Population, Intervention, Comparison and Outcome) and uses keywords based on the database. Result : 4 Studies reviewed based on the specified inclusion criteria, show that the role of emotional intelligence affects the transformational leadership model, with the instrument used referring to the emotional Questions (EQ-i 2.0) instrument used in emotional intelligence, while in transformational leadership using Multi-factor Leadership Question (MLQ) Conclusion : Achieving the desired organizational performance certainly requires a leader who is smart in managing his emotions, so a manager needs to continue to learn in terms of managing his emotional intelligence which has a positive impact on the transformational leadership model used. Key Word : Emotional Intelegency. Transformational Leaderships. Nursing Manager. Sistematic Review